Implementation Deep Breath Techniques Therapy And Possitive Affirmations - Ridho, Ridho; Ajani, Anggra Trisna; Dewi, Debby Silvia; Gusni, Jufrika (Universitas Negeri Padang, 2025)
Lung cancer is a malignant disease that occurs in the lung, either originating from the lung tissue itself (primary) or originating from other organs and spreading to the lung (metastasis). Based on data from the Global Burden of Cancer (Globocan) in 2022, there were 2.4 million cases of lung cancer in the world and resulted in 1.8 million deaths. In Indonesia, data from the Global Cancer Observatory in 2022 showed there were 38,904 lung cancer cases and 34,339 deaths due to this disease. The number of lung cancer cases in Indonesia continues to increase, especially in the West Sumatra region. In Dr. M. Djamil Hospital, from 2021 to 2024, there were 884 cases of lung cancer. The purpose of this case study is to apply nursing care to lung cancer patients admitted to the Lung Inpatient Room of Dr. M. Djamil Padang Hospital in 2025. The results of the assessment of patient Mrs. P showed four nursing problems, namely: ineffective airway clearance, acute pain, nutritional deficits, and activity intolerance. The evaluation showed that some diagnoses were partially resolved, such as tightness and pain that began to decrease, and a body that was no longer weak even though it was still limited in activity. The nursing problem of nutritional deficit is resolved by improving the patient's appetite. After providing nursing care, patients and their families will have knowledge about the causes, signs, symptoms, and complications of lung cancer to improve quality of life and early awareness.